Psychometric testing of the Determinants of Salt-Restriction Behaviour Questionnaire in people of Chinese ancestry: a methodological study - Alex Chan; Leigh Kinsman; Sally Wai-chi Chan (BMC, 2022)
Abstract Purpose Nurses play a key role in educating people about a salt-reduced diet to prevent or manage hypertension or cardiac failure. Assessment tools such as the Chinese Determinants of Salt-Restriction Behaviour Questionnaire (DSRBQ) can provide essential evidence to inform education strategies. This study aimed to translate the DSRBQ into English and evaluate the psychometric properties of the Chinese and English versions for people of Chinese ethnicity in Australia. Methods A two-phase cross-sectional descriptive study was conducted. Phase 1: The questionnaire was translated into English using the back-translation method. The translation equivalence and content relevance were evaluated by an expert panel. Three items were revised and eight items were removed. Phase 2: Internal consistency and stability of the questionnaires were evaluated by a group of Chinese Australians. Results Both the English and Chinese versions had satisfactory psychometric properties. In phase 2, 146 participants completed the questionnaire (test), and 49 participants completed the retest. The Cronbach's alpha scores were 0.638 and 0.584 respectively, and the overall intra-class correlation coefficients were 0.820 and 0.688 respectively for the English and Chinese versions. The Item-Content Validity Index (CVI) ranged from 0.50 to 1.00. The Scale-CVI was 0.94. Conclusion The DSRBQ has been translated into English. Both English and Chinese versions have acceptable validity and reliability. The tools can be used in people from a Chinese cultural background living in Australia. Further validation testing may allow the tools to be adapted for use with other Chinese diaspora groups. The validated DSRBQ will support the development of evidence-based salt reduction nursing assessment tool and interventions for Chinese diasporas who reside in a country where Chinese cultural practices are employed by a minority.